(untitled) (مجلة أبحاث قانونية, 2023)
This research article aims to shed light on the role played today by the finance of the territorial collectivities, so that it contributes to the course of building administrative decentralization in Morocco. The Moroccan legislator deliberately interfered with the competences entrusted to it that were stipulated, whether at the level of constitutional texts, or at the level of the regulatory laws of the territorial collectivities. In addition, the territorial communities today have financial positions that enable them to fulfill their obligations, in addition to having a wide capacity for financing by borrowing, in addition to the important energy of self-resources that are available to some territorial groups that allow them to mobilize additional resources.